Oncological outcomes in minimally invasive vs. open distal pancreatectomy: a systematic review and network meta-analysis - Zhun Hong Wong, Nicky; Wei Ting Yap, Dominic; Lei Ng, Sherryl; Yu Ning Ng, Junie; James, Juanita Jaslin; Wei Chieh Kow, Alfred (Frontiers in Surgery, 2024)
In this network meta-analysis of 9,301 patients with pancreatic ductal adenocarcinoma, oncological outcomes of robotic and laparoscopic approaches of distal pancreatectomies were compared. Findings suggest improvement in overall survival in both minimally invasive approaches when compared to open distal pancreatectomies.Background: Advancements in surgical techniques have improved outcomes in patients undergoing pancreatic surgery. To date there have been no meta-analyses comparing robotic and laparoscopic approaches for distal pancreatectomies (DP) in patients with pancreatic adenocarcinoma (PDAC). This systematic review and network meta-analysis aims to explore the oncological outcomes of laparoscopic distal pancreatectomy (LDP), robotic distal pancreatectomy (RDP) and open distal pancreatectomy (ODP).Methods: A systematic search was conducted for studies reporting laparoscopic, robotic or open surgery for DP. Frequentist network meta-analysis of oncological outcomes (overall survival, resection margins, tumor recurrence, examined lymph nodes, administration of adjuvant therapy) were performed.Results: Fifteen studies totalling 9,301 patients were included in the network meta-analysis.1,946, 605 and 6,750 patients underwent LDP, RDP and ODP respectively. LDP (HR 0.761, 95% CI 0.642-0.901, p=0.002) and RDP (HR 0.757, 95% CI 0.617-0.928, p=0.008) were associated with improved overall survival (OS) benefit when compared to ODP. LDP (HR 1.00, 95% CI 0.793-1.27, p=0.968) was not associated with improved overall survival OS benefit when compared to RDP. There were no significant differences between LDP, RDP and ODP for resection margins, tumor recurrence, examined lymph nodes and administration of adjuvant therapy.This study highlights the improvement in overall survivallonger OS in both LDP and RDP when compared to ODP for patients with PDAC.